2007
DOI: 10.1152/japplphysiol.01235.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-xenon and krypton supplementation on signal/noise of regional CT-based ventilation measurements

Abstract: EA. Effect of low-xenon and krypton supplementation on signal/ noise of regional CT-based ventilation measurements. J Appl Physiol 102: [1535][1536][1537][1538][1539][1540][1541][1542][1543][1544] 2007. First published November 22, 2006; doi:10.1152/japplphysiol.01235.2005.-Xenon computed tomography (Xe-CT) is used to estimate regional ventilation by measuring regional attenuation changes over multiple breaths while rebreathing a constant Xe concentration ([Xe]). Xe-CT has potential human applications, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…Krypton, another radio-opaque inert gas, has a lower attenuation effect than xenon gas, but may be useful for detecting functional alterations in the lungs with DECT because krypton has fewer effects on the body than xenon. To overcome these limitations of xenon, one report showed that a krypton and xenon gas mixture was a better contrast medium than a limited concentration of xenon gas in single energy CT [17]. Another report showed that ventilation DECT with aerosol inhalation of iodinated contrast instead of xenon in animals is feasible, but that the safety of inhaling an iodine contrast medium is unknown [18].…”
Section: Discussionmentioning
confidence: 99%
“…Krypton, another radio-opaque inert gas, has a lower attenuation effect than xenon gas, but may be useful for detecting functional alterations in the lungs with DECT because krypton has fewer effects on the body than xenon. To overcome these limitations of xenon, one report showed that a krypton and xenon gas mixture was a better contrast medium than a limited concentration of xenon gas in single energy CT [17]. Another report showed that ventilation DECT with aerosol inhalation of iodinated contrast instead of xenon in animals is feasible, but that the safety of inhaling an iodine contrast medium is unknown [18].…”
Section: Discussionmentioning
confidence: 99%
“…At the end of each stage, the results are computed and the trial can be stopped if the effectiveness is less than a minimum success rate or greater than an expected success rate (19). The sample size was computed by using the 81m ( 81m Kr) gas used in nuclear medicine for many decades, stable krypton could be an alternative to xenon for ventilation imaging with the use of DE CT. Its clinical tolerance was successfully tested in a few human subjects in the early 1950s (16), and its potential usefulness as a ventilation CT contrast agent, first suggested by Winkler et al (17), was recently reemphasized by Chon et al (18). To our knowledge, this technique has not been used in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Average regional time constants are similar for repeat runs reducing inspired Xe gas concentrations from 55 to 30%, but the coefficient of variation at 30% Xe is significantly greater than at 40% and higher concentrations. The addition of 30% krypton gas to 30% Xe gas provides the same contrast enhancement and signal-to-noise ratio as 40% Xe (155). Krypton has none of the unwanted side effects of higher concentrations of Xe gas.…”
Section: Functional Imagingmentioning
confidence: 99%